2015
DOI: 10.1007/s10646-015-1555-0
|View full text |Cite
|
Sign up to set email alerts
|

Biological toxicity of cellulose nanocrystals (CNCs) against the luxCDABE-based bioluminescent bioreporter Escherichia coli 652T7

Abstract: The aim of this study was to evaluate the biological toxicity of cellulose nanocrystals (CNCs) using the constitutively bioluminescent luxCDABE-based bioreporter Escherichia coli 652T7. The effects of CNCs on E. c oli 652T7 biotoxicity were investigated at different CNC concentrations, reaction times, and IC50 values. CNC toxicity was also compared with and without ultrasonic dispersion to establish dispersibility effects. The results demonstrated that CNCs were not significantly toxic at concentrations at or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
0
24
1
Order By: Relevance
“…Hosseinidoust et al 33 conrmed the biocompatibility of CNC by not detecting any damage or change in density of phagocytic and nonphagocytic cell lines during their interaction with CNC dispersions. Except for some studies 34,35 that showed some minor detrimental effects for highly elevated CNC concentrations (>350 mg l À1 ), CNC still remains a widely accepted versatile biomaterial for producing nature-friendly materials.…”
Section: Introductionmentioning
confidence: 99%
“…Hosseinidoust et al 33 conrmed the biocompatibility of CNC by not detecting any damage or change in density of phagocytic and nonphagocytic cell lines during their interaction with CNC dispersions. Except for some studies 34,35 that showed some minor detrimental effects for highly elevated CNC concentrations (>350 mg l À1 ), CNC still remains a widely accepted versatile biomaterial for producing nature-friendly materials.…”
Section: Introductionmentioning
confidence: 99%
“…Lower bioavailability of the Hg(II) ions would be connected not only with the lower bioluminescence induction, but possibly also with lower toxic effect of the mercury on the E. coli ARL1. The decrease of Hg 2+ -induced bioluminescent response of strain ARL1 in the presence of humic acids was ascribed to reduction of bioavailability of Hg 2+ via complexation with HA also by Du et al [46]. The comparison of the growth rates (Table 3) helped us to elucidate the humic acid action.…”
Section: Mercury Arl1 Bioassay and Its Interferencesmentioning
confidence: 59%
“…This assumption is supported by the lux-mer construction which uses the detoxification-elimination mechanism. Low toxicity of complexes with humic acids to E. coli was already shown by unchanged light emission of constitutive bioreporter E. coli 652T7 [46]. As a result, the positive effect of humic acid on the bacterial growth cannot be explained by protecting the cells from the toxicity of mercury by its binding.…”
Section: Mercury Arl1 Bioassay and Its Interferencesmentioning
confidence: 99%
“…In general, environmental conditions have a large potential for mediating the toxicity of engineered nanoparticles. Du et al (2015) evaluated the toxicity of cellulose nanocrystals (CNCs) by assessment of the response of constitutively bioluminescent luxCDABEbased bioreporter Escherichia coli 652T7. Results demonstrated that CNCs were not significantly toxic at concentrations at or below 250 mg/L, but the toxicity increased linearly as CNC concentrations increased from 300 to 2000 mg/L.…”
Section: Toxic Effect Of Engineered Nanoparticlesmentioning
confidence: 99%